What do women want? Linguistic equality and the feminization of job titles in contemporary France - van Compernolle, Rémi A. (Gender and Language, 2009)
This article examines young French women's perceptions with regard to the grammatical feminization of professional titles, drawing from data collected during semi-guided one-to-one interviews. A qualitative analysis of the interviews is presented, focusing specifically on three recurring themes: (i) feminization as a move toward equality between men and women, (ii) the questioning of the existence of feminized neologisms, and (iii) the role of the French government in legislating linguistic change. It is argued that feminization is not a matter of pro- versus anti-feminization arguments; rather, a complex of sociocultural and linguistic factors is at work, which has not been fully teased out in previous quantitative studies. In concluding, the results are discussed within the broader context of ongoing linguistic changes in the French language and directions for future research are proposed.